Problematika Guru dalam Pembelajaran SKI di SD Nurul Islam Medan - Nasution, Abdul Gani Jamora; Matondang, Aflah Husnaini; Nurhafizah, Nurhafizah; Siregar, Nurhaliza Ertays; Harahap, Novia Rahmadani (Lembaga Yasin AlSys, 2023)
The purpose of this study is to be able to find out the teacher's problems in SKI learning at SD Nurul Islam Indonesia, Medan. The type of research used in this research is descriptive qualitative research which prioritizes the use of data in the field. Descriptive qualitative research is research that describes the situation to be studied thoroughly, broadly, and in depth. The results showed that the problems teachers faced in learning SKI at SD Nurul Islam Indonesia were, first, the teacher's lack of understanding in mastering SKI learning material. Second, the methods and strategies that teachers use seem boring. third, the lack of facilities and infrastructure to support the teaching and learning process. Fourth, the limited time in the SKI learning process.